Implication of alpha-Klotho as the predictive factor of stress - Nakanishi, Kaori; Nishida, Makoto; Taneike, Manabu; Yamamoto, Ryohei; Adachi, Hiroyoshi; Moriyama, Toshiki; Yamauchi-Takihara, Keiko (Journal of investigative medicine, 2019)
Stress is known as a risk factor for both mental and physical health problems. While stress is known as one of the major health problems in modern society, a biomarker of stress has not yet been well established. In the present study, we focused on the serum levels of α-Klotho (αKl) as a possible objective biomarker of stress. Subjects included apparently healthy individuals who underwent a health examination in the Osaka University Health and Counseling Center. Physical and biochemical parameters were obtained from all subjects. Information regarding the lifestyle of each individual was obtained via questionnaires. Among male subjects, serum levels of soluble αKl (sαKl) were significantly elevated in subjects who had poor stress management and unsatisfactory sleep, suggesting that stress management and sleeping conditions influenced the serum levels of sαKl. The total Kessler Screening Scale for Psychological Distress (K6) score was significantly increased in subjects who reported experiencing considerable stress, had poor stress management and unsatisfactory sleep. Since serum levels of sαKl showed the same tendency as the K6 score in terms of the relationship between stress management and sleeping conditions in male subjects, increased sαKl levels could be associated with considerable psychological stress in healthy men.